Laminate, heat insulating material and vacuum heat insulating container, and method for producing laminate
A laminate with a thermoplastic resin fiber layer and metal-containing resin layer, featuring through holes, addresses wrinkles and enhances insulation performance in vacuum environments by improving radiant heat reflectivity and breathability.
Patent Information
- Application Number
- JP2023092160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing heat insulating sheets experience wrinkles that reduce radiant heat reflectivity, leading to decreased insulation performance, and there is a need for improved insulation performance in vacuum environments.
A laminate composed of a fiber layer made of thermoplastic resin fibers with a thermoplastic resin layer containing metal, featuring through holes and specific thickness and density ratios, enhancing radiant heat reflectivity and insulation performance.
The laminate achieves high radiant heat reflectivity and excellent heat insulation properties while maintaining breathability, suitable for vacuum or low-pressure environments.
Smart Images

Figure 2024174364000001 
Figure 2024174364000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, a thermal insulation material, a vacuum insulated container, and a method for producing the laminate. [Background technology]
[0002] When storing and transporting liquefied gas such as liquid nitrogen, vacuum insulation is generally used as a means for maintaining a cryogenic state. For example, Patent Document 1 proposes a heat insulating sheet as a heat insulating material used in such a vacuum environment or low pressure environment, which includes a resin film having a metal layer and a nonwoven fabric containing resin fibers, which are joined together with through holes, and in which the ratio of the average distance between the through holes in the resin film and the average distance between the through holes in the nonwoven fabric is within a specific range. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 181186 Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the heat insulating sheet disclosed in Patent Document 1, the ratio of the average distance between the through holes in the resin film and the average distance between the through holes in the nonwoven fabric is set to a specific range, so that the resin film having a metal layer tends to wrinkle easily. When wrinkles occur in the resin film having a metal layer, the reflectivity of radiant heat is reduced, and there is a problem that the heat insulating performance cannot be fully exhibited. In addition, the required level of heat insulating performance is becoming stricter year by year, and further performance improvement is required.
[0005] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a laminate having high radiant heat reflectivity and excellent heat insulating properties. [Means for solving the problem]
[0006] In order to achieve the above object, the present inventors have attempted to improve the reflectance in a manner that does not intentionally cause wrinkles. However, it has been confirmed that suppressing the occurrence of wrinkles improves the reflectance but deteriorates the heat insulating performance. As a result of further intensive research, it has been found that in a laminate including a fiber layer composed of fibers mainly composed of thermoplastic resin and a thermoplastic resin layer containing metal, when a through hole is provided through the fiber layer and the thermoplastic resin layer, and further, when the ratio of the thickness of the fiber layer to the thickness of the thermoplastic resin layer and the apparent density of the laminate are within a specific range, the reflectance of radiant heat can be improved, and further, the heat insulating performance when used as a heat insulating material can be improved. In addition, it has been found that this laminate can achieve both heat insulating property and breathability.
[0007] The present invention has been completed based on these findings, and provides the following inventions.
[0008] [1] A fiber layer composed of fibers mainly composed of thermoplastic resin; A thermoplastic resin layer containing a metal; A laminate comprising: the laminate has through holes penetrating the fiber layer and the thermoplastic resin layer, The ratio of the thickness of the fiber layer to the thickness of the thermoplastic resin layer is 5 or more and 40 or less; The apparent density of the laminate is 0.10 g / cm 3 More than 0.35g / cm 3 Below is the Laminate.
[0009] [2] The laminate according to [1], wherein the through holes have a diameter of 100 μm or more and 2000 μm or less, and an aperture ratio of the through holes is 0.05% or more and 9.00% or less.
[0010] [3] The laminate according to [1] or [2], wherein one of the outermost layers of the laminate is the fiber layer, and the arithmetic mean roughness Ra of the outermost layer on the fiber layer side is 3.0 μm or more and 30.0 μm or less.
[0011] [4] The laminate according to [1] or [2], wherein one of the outermost layers of the laminate is the thermoplastic resin layer, and the arithmetic mean roughness Ra of the outermost layer on the thermoplastic resin layer side is 0.01 μm or more and less than 3.00 μm.
[0012] [5] The laminate according to [1] or [2], wherein one outermost layer of the laminate is the fiber layer, and the arithmetic mean roughness Ra of the outermost layer on the fiber layer side is 3.0 μm or more and 30.0 μm or less, and the other outermost layer of the laminate is the thermoplastic resin layer, and the arithmetic mean roughness Ra of the outermost layer on the thermoplastic resin layer side is 0.01 μm or more and less than 3.00 μm.
[0013] [6] The laminate according to any one of the above [1] to [5], further comprising a metal layer containing aluminum on at least one surface of the thermoplastic resin layer.
[0014] [7] The laminate according to any one of the above [1] to [6], wherein one of the outermost layers of the laminate is a long-fiber nonwoven fabric layer.
[0015] [8] A heat insulating material comprising the laminate according to any one of [1] to [7] above.
[0016] [9] A vacuum insulated container using the insulating material described in [8] above.
[0017]
[10] A method for producing a laminate according to any one of the above [1] to [7], comprising a step of heat-sealing the fiber layer and the thermoplastic resin layer.
[0018]
[11] The method for producing a laminate according to
[10] above, wherein the fiber layer and the thermoplastic resin layer are thermally fused together by penetrating them with a heated projection. Effect of the Invention
[0019] According to the present invention, a laminate can be obtained which is easy to produce, has excellent heat insulating properties due to its high radiant heat reflectivity, and also has excellent breathability. Due to these properties, the laminate of the present invention can be suitably used as a heat insulating material, particularly in a vacuum or low pressure environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] These components of the present invention will be described in detail below, but the present invention is not limited to the embodiments described below.
[0021] [Fiber layer] The laminate of the present invention includes a fiber layer composed of fibers mainly composed of a thermoplastic resin. In the present invention, the term "fibers mainly composed of a thermoplastic resin" refers to fibers in which the mass ratio of the thermoplastic resin is 60 mass% or more.
[0022] (1)Thermoplastic resin Examples of the thermoplastic resin that is the main component of the fibers that constitute the fiber layer of the laminate of the present invention include polyester-based resins and polyolefin-based resins.
[0023] The polyester resin is mainly composed of a polymer obtained by polycondensation of an acid component and an alcohol component, or a polymer obtained by ring-opening polymerization of lactone or lactide. Here, the term "main component" means that it accounts for 60% by mass or more of the entire polyester resin. Examples of the acid component include aromatic carboxylic acids such as phthalic acid (ortho form), isophthalic acid, and terephthalic acid, aliphatic dicarboxylic acids such as adipic acid and sebacic acid, and alicyclic dicarboxylic acids such as cyclohexane carboxylic acid. Examples of the alcohol component include ethylene glycol, diethylene glycol, and polyethylene glycol. Examples of the lactone include β-propiolactone and ε-caprolactone.
[0024] Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polylactic acid (PLA), polybutylene succinate (PBS), and copolymer polyester resins based on these. Of these, PET is preferably used because it has high spinnability and forms a fiber layer with excellent quality.
[0025] The melting point of the polyester resin is preferably 200°C or more and 320°C or less. The melting point of the polyester resin is preferably 200°C or more, more preferably 220°C or more, and even more preferably 240°C or more, so that the fiber layer has excellent heat resistance, and as a result, the laminate has excellent heat resistance. On the other hand, the melting point of the polyester resin is preferably 320°C or less, more preferably 300°C or less, and even more preferably 280°C or less, so that the energy consumption during the production of the fiber layer is reduced and the yarn discharged from the spinneret can be easily cooled. Therefore, when a nonwoven fabric is used as a preferred embodiment of the fiber layer described later, the fusion between the fibers is suppressed, and the nonwoven fabric has excellent uniformity of texture, and as a result, when used as a heat insulating material, the laminate has uniform heat insulating performance.
[0026] The intrinsic viscosity (IV) of the polyester resin is preferably 0.55 or more and 0.75 or less. By making the intrinsic viscosity (IV) preferably 0.55 or more, more preferably 0.60 or more, and even more preferably 0.62 or more, the single fiber strength can be improved. On the other hand, by making the intrinsic viscosity (IV) preferably 0.75 or less, more preferably 0.70 or less, and even more preferably 0.68 or less, the spinnability is high and a fiber layer with excellent quality can be obtained.
[0027] In the present invention, the intrinsic viscosity (IV) of the polyester resin is a value measured by the following method. (i) Dissolve 8 g of sample in 100 mL of orthochlorophenol, and measure the relative viscosity η at 25°C using an Ostwald viscometer. r is calculated using the following formula: η r =η / η0=(t×d) / (t0×d0) Here, η: Viscosity of the polymer solution η0: Viscosity of orthochlorophenol t: Time it takes for the solution to fall (seconds) d: density of the solution (g / cm 3 ) t0: Time it takes for orthochlorophenol to fall (seconds) d0: Density of orthochlorophenol (g / cm 3 ) (ii) Relative viscosity η r Calculate the intrinsic viscosity (IV) using the following formula and round off to the third decimal place. Intrinsic viscosity (IV)=0.0242η r +0.2634.
[0028] Examples of the polyolefin resin include polyethylene resin, polypropylene resin, polybutene resin, polymethylpentene resin, and copolymerized polyolefin resin based on these resins. Among them, polyethylene resin and polypropylene resin are preferred because they have high spinnability and can form a fiber layer with excellent quality, and polypropylene resin is more preferred.
[0029] The polyethylene resin means a resin in which the molar fraction of ethylene units in the repeating units is 60 mol% to 100 mol%. Examples of the polyethylene resin include homopolymers of ethylene and copolymers of ethylene and various α-olefins. Among them, homopolymers of ethylene are preferred in order to prevent a decrease in spinning stability and strength. As the copolymers of ethylene and various α-olefins, copolymers of ethylene and α-olefins having 3 to 5 carbon atoms are preferred. As the α-olefins having 3 to 5 carbon atoms, propylene, 1-butene, and 1-pentene are preferred, with 1-butene being more preferred. In this way, entanglement of molecular chains during melting is suppressed, thread breakage is suppressed, and the increase in amorphous components can be prevented, which causes the sheet to stick to the roll during heat bonding, and the sheet to have unevenness or wrinkles, thereby preventing a decrease in quality.
[0030] When the copolymer of ethylene and various α-olefins is used, the content of the α-olefin is preferably 0.1 mol% to 10 mol% based on the polymerization components of the polyethylene resin. By making the content of the α-olefin preferably 0.1 mol% to 10 mol%, more preferably 0.1 mol% to 7 mol%, and even more preferably 0.1 mol% to 5 mol%, it is possible to prevent a decrease in spinning stability and to prevent the sheet from sticking to a roll during thermal adhesion, which causes unevenness or wrinkles in the sheet, thereby preventing a decrease in quality, and therefore a laminate with uniform thermal insulation performance is obtained when used as a thermal insulation material. The type of α-olefin and the content of α-olefin in the polymerization components of the polyethylene resin can be calculated, for example, from the peak position and peak area ratio detected by a nuclear magnetic resonance (NMR) device.
[0031] Examples of the polyethylene resin include medium density polyethylene, high density polyethylene (hereinafter sometimes abbreviated as HDPE), linear low density polyethylene (hereinafter sometimes abbreviated as LLDPE), etc. Among them, HDPE or LLDPE is preferably used because it has high spinnability and forms a fiber layer with excellent quality.
[0032] The melting point of the polyethylene resin is preferably 100° C. or higher and 150° C. or lower. The melting point is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher, so that the laminate has heat resistance that can withstand practical use. The melting point is preferably 150° C. or lower, more preferably 140° C. or lower, and even more preferably 135° C. or lower, so that the fibers discharged from the spinneret can be easily cooled, and when a nonwoven fabric is used as a preferred embodiment of the fiber layer described below, the fusion of the fibers is suppressed, resulting in a nonwoven fabric with excellent uniformity of texture, and as a result, a laminate with uniform heat insulating performance when used as a heat insulating material.
[0033] The solid density of the polyethylene resin is 0.935 g / cm 3 More than 0.970g / cm 3 The solid density is preferably 0.935 g / cm or less. 3 More preferably, 0.940 g / cm 3 More preferably, 0.945 g / cm 3 By satisfying the above, when a nonwoven fabric is used as a preferred embodiment of the fiber layer described below, the occurrence of unevenness or wrinkles due to sticking to a hot embossing roll can be prevented when the nonwoven fiber web is fused to obtain a nonwoven fabric, and therefore a laminate having excellent heat insulating performance can be obtained when used as a heat insulating material. 3 Less than or equal to 0.965 g / cm 3 More preferably, 0.960 g / cm 3 When the fiber is spun at or below this condition, spinnability is increased, resulting in a fiber layer of excellent quality, and as a result, a laminate having excellent heat insulating performance when used as a heat insulating material.
[0034] The polypropylene resin means a resin in which the molar fraction of propylene units in the repeating units is 60 mol% to 100 mol%. Examples of the polypropylene resin include a homopolymer of propylene, a copolymer of propylene with ethylene, and various α-olefins. Among them, a homopolymer of propylene is preferred in order to prevent a decrease in spinning stability and strength.
[0035] When a copolymer of propylene and various α-olefins is used as the polypropylene-based resin, the copolymerization component is preferably ethylene or 1-butene, more preferably ethylene, because of its excellent spinning stability. The copolymerization ratio is preferably 15 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less, in order to prevent a decrease in spinning stability and strength.
[0036] The α-olefin species and the α-olefin content in the polymerization components of the polypropylene resin can be calculated, for example, from the peak positions and peak area ratios detected by a nuclear magnetic resonance (NMR) spectrometer.
[0037] The melting point of the polypropylene resin is preferably 120°C or higher and 180°C or lower. The melting point is preferably 120°C or higher, more preferably 130°C or higher, and even more preferably 140°C or higher, so that heat resistance sufficient for practical use can be easily obtained, resulting in a laminate with excellent heat resistance. In addition, the melting point is preferably 180°C or lower, more preferably 170°C or lower, and even more preferably 160°C or lower, so that the fibers discharged from the spinneret can be easily cooled, and when a nonwoven fabric is used as a preferred embodiment of the fiber layer described below, the fusion between the fibers can be suppressed to form a fiber layer with excellent uniformity of texture, resulting in a laminate with uniform heat insulation performance when used as a heat insulating material.
[0038] The thermoplastic resin may be a mixture of two or more kinds, but in order to fully express the properties of the main thermoplastic resin, the ratio of the other thermoplastic resin to be mixed is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0039] The melt flow rate (hereinafter sometimes abbreviated as MFR) of the thermoplastic resin is preferably 1 g / 10 min or more and 300 g / 10 min or less. The MFR is preferably 1 g / 10 min or more, more preferably 10 g / 10 min or more, and even more preferably 20 g / 10 min or more, so that the spinnability is high, and therefore a fiber layer with excellent quality can be obtained, and as a result, when used as a heat insulating material, a laminate with uniform heat insulating performance can be obtained. On the other hand, the MFR is preferably 300 g / 10 min or less, more preferably 200 g / 10 min or less, and even more preferably 100 g / 10 min or less, so that the decrease in single fiber strength can be suppressed, and a fiber layer with excellent strength and rigidity can be obtained, and as a result, a laminate with excellent durability can be obtained. Of course, the MFR of the thermoplastic resin used in the present invention can also be adjusted by blending two or more resins with different MFRs in any ratio.
[0040] The MFR of a thermoplastic resin is a value measured by ASTM D1238 (Method A). This standard specifies that polyethylene should be measured at a load of 2.16 kg and a temperature of 190° C., and polypropylene should be measured at a load of 2.16 kg and a temperature of 230° C. When measuring the MFR of a thermoplastic resin from a laminate, the thermoplastic resin layer described below should be separated and then measured by the above method.
[0041] Furthermore, to the thermoplastic resin, additives such as commonly used antioxidants, weather resistance stabilizers, light resistance stabilizers, heat resistance stabilizers, antistatic agents, electrostatic assistants, spinning agents, antiblocking agents, matting agents, antibacterial agents, antifungal agents, antiallergen agents, antiviral agents, vitamins, flame retardants, metal oxides, hydrophilic agents, crystal nucleating agents, pigments, lubricants including polyethylene wax, aliphatic bisamides and / or aliphatic monoamides, or other polymers may be added, provided the effects of the present invention are not impaired.
[0042] (2) Fibers The fibers constituting the fiber layer of the laminate of the present invention are mainly composed of the thermoplastic resin. The cross-sectional shape of the fiber can be a round cross-section, a flat cross-section, or an irregular cross-section such as a Y-shape or a C-shape. Among them, a round cross-section is a preferred embodiment because it is possible to obtain a fiber layer with excellent flexibility without the difficulty in bending due to the structure of a flat cross-section or an irregular cross-section. A hollow cross-section can also be applied as the cross-sectional shape, but a solid cross-section is a preferred embodiment because it is highly spinnable and provides a fiber layer with excellent quality.
[0043] The fibers may be composite fibers made of two or more thermoplastic resins in order to improve the strength and flexibility of the fiber layer. The composite form of the composite fiber may be, for example, a concentric core-sheath type, an eccentric core-sheath type, an island-in-the-sea type, or a side-by-side type. Among them, a concentric core-sheath type composite form is preferred because it has high spinnability and produces a fiber layer with excellent quality.
[0044] (3) Fiber layer The laminate of the present invention comprises a fiber layer composed of the above-mentioned fibers, which allows precise control of the internal voids and surface condition of the laminate, resulting in a laminate with excellent heat insulation properties, breathability, and workability.
[0045] The fiber layer may be a nonwoven fabric, woven fabric, or knitted fabric, and is preferably a nonwoven fabric because of its high strength, durability, and productivity. Examples of the nonwoven fabric include dry nonwoven fabrics produced by the carding method or airlaid method, wet nonwoven fabrics produced by papermaking, and long fiber nonwoven fabrics (direct spun nonwoven fabrics) produced by accumulating fibers that have been directly spun (melt blown method, spunbond method).
[0046] Among these, it is preferred that the layer forming the surface of the laminate (the fiber layer that is one of the outermost layers of the laminate in the first and third embodiments described below) is a long-fiber nonwoven fabric layer, in particular a spunbond nonwoven fabric layer obtained by a spunbonding method, because this results in a laminate with higher strength and durability and the productivity of the fiber layer itself is also excellent.
[0047] The mass per unit area of the fiber layer is 5 g / m 2 More than 50g / m 2 The basis weight is preferably 5 g / m or less. 2 More preferably, 10 g / m 2 More preferably, 15 g / m 2 By satisfying the above, a laminate having sufficient strength for practical use can be obtained. On the other hand, the basis weight is preferably 50 g / m 2 Less than 40 g / m 2 More preferably, 30 g / m or less 2 By satisfying the above condition, the laminate can maintain flexibility and have excellent conformability even to complex shapes, and can further improve workability when used as a thermal insulation material. When a laminated fiber layer is used as the fiber layer, the basis weight of the entire laminated fiber layer is measured.
[0048] In the present invention, the mass per unit area (basis weight) of the fiber layer is determined in accordance with "6.2 Mass per unit area" of JIS L1913:2010 "Testing methods for general nonwoven fabrics" and is measured by the following procedure. (i) Take 20 cm x 25 cm test pieces (in the case of measuring a laminate, the thermoplastic resin layer described below is separated, etc.) and take three pieces per meter of sample width. (ii) Weigh the mass (g) of each at standard conditions. (iii) The average value is 1 m 2 Mass per unit (g / m 2 )
[0049] In the laminate of the present invention, the ratio of the mass per unit area of the fiber layer to the mass per unit area of the laminate (hereinafter, sometimes simply abbreviated as "mass ratio of the fiber layer") is preferably 30% by mass or more and 90% by mass or less. By making the mass ratio of this fiber layer preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more, the thermoplastic resin layers in the laminate can be prevented from contacting each other, and the laminate can have excellent heat insulation properties. On the other hand, by making the mass ratio of the fiber layer 90% by mass or less, the thermoplastic resin layer can maintain sufficient strength and prevent a decrease in the reflectivity of radiant heat.
[0050] The fiber layer preferably has a fused portion and a non-fused portion. The fused portion refers to a portion where the fibers are compressed in the thickness direction of the fiber layer and deformed to fuse with each other, and the non-fused portion refers to a portion other than the fused portion. In this way, the laminate can be made flexible and conformable to a complex shape when used as a heat insulating material, and can be given sufficient strength for practical use, resulting in a laminate with better workability. In addition, since the apparent density is different between the fused portion and the non-fused portion, it is possible to form unevenness on the surface, and when a plurality of the laminates of the present invention are stacked and used as a heat insulating material, the thermal conduction between the laminates can be reduced.
[0051] The thickness of the fiber layer is preferably 50 μm or more and 250 μm or less. By making the thickness preferably 50 μm or more, more preferably 60 μm or more, and even more preferably 80 μm or more, it is possible to improve the heat insulating property and to make the handling excellent. On the other hand, by making the thickness preferably 250 μm or less, more preferably 230 μm or less, and even more preferably 200 μm or less, it is possible to maintain flexibility and conform to complicated shapes when used as a heat insulating material, and it is possible to save space by being a thin film.
[0052] In the present invention, the thickness (mm) of the fiber layer is a value measured by the following procedure. However, when a laminated fiber layer is used as the fiber layer, the thickness of the entire laminated fiber layer is defined as the thickness of the fiber layer. (i) Using a pressure probe with a diameter of 10 mm (for example, "SM-114" manufactured by Techclock Corporation), measure the thickness to the nearest 0.001 mm at 10 points per meter at equal intervals across the width of the laminate under a load of 10 kPa. (ii) The arithmetic mean value (mm) of the values obtained in (i) is calculated and rounded off to the third decimal place. This value is then converted to μm, and this value is used as the thickness (μm) of the laminate. (iii) The thickness (μm) of the thermoplastic resin layer is calculated by the method described in the section on thermoplastic resin layer below. (iv) The difference (μm) between the thickness (μm) of the laminate and the thickness (μm) of the thermoplastic resin layer is calculated.
[0053] The thickness of the fiber layer can be controlled by appropriately adjusting the average single fiber diameter of the fiber, the basis weight of the fiber layer, and / or the thermal bonding conditions (shape of the bonded part, compression rate, temperature, linear pressure, etc.) described below.
[0054] Furthermore, the apparent density of the fiber layer is 0.05 g / cm 3 More than 0.60g / cm 3 The apparent density is preferably 0.05 g / cm or less. 3 More preferably, 0.08 g / cm 3More preferably, 0.10 g / cm 3 By satisfying the above requirements, it is possible to obtain a laminate having reduced fuzzing and having strength and ease of handling. On the other hand, the apparent density is preferably 0.60 g / cm 3 Less than or equal to 0.50 g / cm 3 More preferably, 0.40 g / cm 3 By satisfying the above condition, it is possible to prevent a decrease in voids inside the laminate, which would result in a decrease in heat insulating properties, and a loss in flexibility of the laminate.
[0055] In the present invention, the apparent density (g / cm 3 ) is calculated from the above unrounded basis weight and thickness according to the following formula, and rounded off to the third decimal place. Apparent density (g / cm 3 )=[Weight (g / m 2 )] / [Thickness (μm)].
[0056] The apparent density can be controlled by appropriately adjusting the average single fiber diameter of the fibers, the basis weight of the fiber layer, the thickness of the fiber layer, and / or the thermal bonding conditions (shape of the bonded part, compression rate, temperature, linear pressure, etc.) described below.
[0057] [Thermoplastic resin layer] The laminate of the present invention comprises the above-mentioned fiber layer and a thermoplastic resin layer containing a metal.
[0058] (1)Thermoplastic resin The thermoplastic resin layer preferably contains a thermoplastic resin as a main component. In the present invention, "containing a thermoplastic resin as a main component" means that the mass ratio of the thermoplastic resin is 60 mass% or more. Examples of the thermoplastic resin include polyester resin, polyolefin resin, polyamide resin, etc.
[0059] The thermoplastic resin may be a mixture of two or more kinds, but in order to fully express the properties of the main thermoplastic resin, the ratio of the other thermoplastic resin to be mixed is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.
[0060] (1-1) Polyester resin The polyester resin mainly comprises a polymer obtained by polycondensation of an acid component and an alcohol component, or a polymer obtained by ring-opening polymerization of lactone or lactide. Examples of the acid component include aromatic carboxylic acids such as phthalic acid (ortho form), isophthalic acid, and terephthalic acid, aliphatic dicarboxylic acids such as adipic acid and sebacic acid, and alicyclic dicarboxylic acids such as cyclohexane carboxylic acid. Examples of the alcohol component include ethylene glycol, diethylene glycol, and polyethylene glycol. Examples of the lactone include β-propiolactone and ε-caprolactone.
[0061] Specific examples of the polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), polylactic acid (PLA), polybutylene succinate (PBS), and copolymer polyester resins based on these.
[0062] The polyester resin preferably has a melting point of 200° C. or higher. When the polyester resin has a melting point of preferably 200° C. or higher, more preferably 220° C. or higher, and further preferably 240° C. or higher, it becomes a thermoplastic resin layer such as a film or extrusion laminate that has excellent heat resistance and can withstand deposition processing, and becomes a laminate with excellent radiant heat reflectivity.
[0063] (1-2) Polyolefin resin On the other hand, examples of the polyolefin resin include polyethylene resin, polypropylene resin, polybutene resin, polymethylpentene resin, and copolymer polyolefin resins based on these resins.
[0064] Here, the polyethylene resin refers to a resin in which the molar fraction of ethylene units in the repeating units is 60 mol % to 100 mol %. Examples of the polyethylene resin include a homopolymer of ethylene and a copolymer of ethylene and various α-olefins.
[0065] The melting point of the polyethylene resin is preferably 100° C. or higher. When the melting point is preferably 100° C. or higher, more preferably 110° C. or higher, and further preferably 120° C. or higher, the resin becomes a thermoplastic resin layer such as a film or extrusion laminate that has excellent heat resistance and can withstand deposition processing, and a laminate that has excellent reflectivity of radiant heat.
[0066] The polypropylene resin means a resin in which the molar fraction of propylene units in the repeating units is 60 mol% to 100 mol%. Examples of the polypropylene resin include a homopolymer of propylene, a copolymer of propylene with ethylene, and various α-olefins.
[0067] The melting point of the polypropylene resin is preferably 120° C. or higher. By setting the melting point to be preferably 120° C. or higher, more preferably 130° C. or higher, and further preferably 140° C. or higher, a thermoplastic resin layer such as a film or extrusion laminate that is excellent in heat resistance and can withstand deposition processing is obtained, and a laminate with excellent reflectivity of radiant heat is obtained.
[0068] (1-3) Polyamide resin The polyamide resin means a resin in which 60% by mass or more of a polymer having an acid amide bond in the chain is obtained by ring-opening polymerization of a lactam having three or more members or polycondensation of a polymerizable ω-amino acid, a dibasic acid and a diamine. As the lactam having three or more members, α-pyrrolidone, α-piperidone, ε-caprolactam, enantholactam, etc. can be used. As the ω-amino acid, aminocaproic acid, 7-aminoheptanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, etc. can be used. As the dibasic acid, terephthalic acid, isophthalic acid, adipic acid, sebacic acid, dodecane dibasic acid, glutaric acid, etc. can be used, and as the diamine, diamines such as hexamethylenediamine, nonamethylenediamine, undecamethylenediamine, dodecamethylenediamine, and metaxylenediamine can be used.
[0069] Specific examples of the polyamide resin include polyamide 4, polyamide 6, polyamide 7, polyamide 8, polyamide 11, polyamide 12, polyamide 6·6, polyamide 6·10, polyamide 6·11, polyamide 6·12, polyamide 6T, polyamide 6 / 6·6, polyamide 6 / 12, polyamide 6 / 6T, and polyamide 6I / 6T.
[0070] The melting point of the polyamide resin is preferably 200° C. or higher. When the melting point of the polyamide resin is preferably 200° C. or higher, more preferably 220° C. or higher, and further preferably 240° C. or higher, the polyamide resin becomes a thermoplastic resin layer such as a film or extrusion laminate that has excellent heat resistance and can withstand deposition processing, and becomes a laminate with excellent reflectivity of radiant heat.
[0071] (2) Thermoplastic resin layer The laminate of the present invention comprises a thermoplastic resin layer containing a metal. Specific embodiments of this thermoplastic resin layer include a film or an extrusion laminate mainly composed of the thermoplastic resin. Here, "mainly composed of the thermoplastic resin" means that the thermoplastic resin accounts for 60% by mass or more of the entire thermoplastic resin layer.
[0072] As the thermoplastic resin layer, at least one selected from the group consisting of a thermoplastic resin layer made of a thermoplastic resin containing a metal as described above and a thermoplastic resin layer the surface of which is coated with a metal layer is preferred. Among these, the thermoplastic resin layer is preferably a thermoplastic resin layer the surface of which is coated with a metal layer, because it has excellent reflectivity against radiant heat.
[0073] When a film having a surface covered with a metal layer is used as the thermoplastic resin layer, the film may be either a non-porous film or a microporous film.
[0074] The metal layer may be made of, for example, a metal containing aluminum, copper, zinc, gold, silver, chromium, platinum, nickel, etc. Among these, a metal containing aluminum is preferable because it is easy to handle and has excellent reflectivity against radiant heat.
[0075] When the metal layer contains aluminum, the aluminum content is preferably 10% by mass or more. By making the aluminum content preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 50% by mass or more, particularly preferably 70% by mass or more, and most preferably 90% by mass or more, it is possible to improve the reflectivity of radiant heat.
[0076] The thickness of the metal layer is preferably 10 nm or more and 300 nm or less. When the thickness of the metal layer is preferably 10 nm or more, more preferably 50 nm or more, and even more preferably 100 nm or more, the laminate has excellent radiant heat reflectivity. On the other hand, when the thickness of the metal layer is preferably 300 nm or less, more preferably 250 nm or less, and even more preferably 200 nm or less, the laminate retains flexibility and has excellent conformability to complex shapes when used as a heat insulating material.
[0077] The thickness of the metal layer is measured and calculated by the following method. (1) Ten small sample pieces (10 mm x 10 mm) are randomly taken from the laminate, and a cross-sectional sample in the horizontal direction is cut out from each small sample piece. (2) The cross section of the test piece is observed using a transmission electron microscope (TEM, for example, JEM-F200 manufactured by JEOL Ltd.), and the thickness (nm) of the metal layer is measured at five locations on each sample, for a total of 50 locations. (3) The thickness values of the metal layer measured at 50 locations are averaged and rounded off to the first decimal place to obtain the thickness of the metal layer (nm).
[0078] The thickness of the metal layer can be controlled by appropriately adjusting the conditions (time, degree of vacuum, processing strength) of the metal layer forming process such as vapor deposition or sputtering.
[0079] The thickness of the thermoplastic resin layer is preferably 1 μm or more and 50 μm or less. By making the thickness preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more, the strength of the laminate is improved, and the laminate has excellent handleability. On the other hand, by making the thickness preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less, the laminate retains flexibility and has excellent conformability to complex shapes when used as a heat insulating material, which further improves the workability when used as a heat insulating material, and the thin film allows space saving.
[0080] The thickness (μm) of the thermoplastic resin layer is determined by the following procedure. (i) Ten small sample pieces (10 mm x 10 mm) are randomly taken from the laminate, and a cross-sectional sample in the horizontal direction is cut out from each small sample piece. (ii) The cross section of the test piece is observed using a scanning electron microscope (SEM, for example, "VHX-D500" manufactured by Keyence Corporation) or a transmission electron microscope (TEM, for example, "JEM-F200" manufactured by JEOL Ltd.), and the thickness (μm) of the thermoplastic resin layer is measured at five locations on each sample, for a total of 50 locations. (iii) The thickness values of the thermoplastic resin layer measured at 50 locations are averaged, and the average is rounded off to the first decimal place to obtain the thickness (μm) of the thermoplastic resin layer.
[0081] The mass per unit area of the thermoplastic resin layer is 1 g / m 2 More than 30g / m 2 The basis weight is preferably 1 g / m or less. 2 More preferably, 3 g / m 2 More preferably, 5 g / m 2 By satisfying the above requirements, a laminate having sufficient strength for practical use can be obtained. On the other hand, the basis weight is preferably 30 g / m 2 Less than or equal to 25 g / m 2 More preferably, 20 g / m or less 2 By satisfying the above condition, the laminate can retain flexibility and have excellent conformability even to complex shapes, thereby further improving workability when used as a thermal insulation material.
[0082] In the present invention, the mass per unit area (weight per unit area) of the thermoplastic resin layer is a value measured in the same manner as the mass per unit area (weight per unit area) of the fiber layer (when measuring from the laminate, the fiber layer is separated, etc.).
[0083] [Laminate] The laminate of the present invention is a laminate comprising the fiber layer and the thermoplastic resin layer. The laminate of the present invention may comprise a plurality of the fiber layers or a plurality of the thermoplastic resin layers. The laminate has a through hole penetrating the fiber layer and the thermoplastic resin layer. The through hole refers to a hole (hereinafter, referred to as an opening) in the thermoplastic resin layer, which penetrates not only the thermoplastic resin layer but also the fiber layer (the position of the hole in the thermoplastic resin layer and the position of the hole in the fiber layer are the same). It is preferable that the ratio of the through holes among the openings in the entire laminate is 30% or more. In addition, pieces of the thermoplastic resin layer generated when the holes are opened may remain inside the openings. The through holes may be arranged regularly or irregularly. Among them, it is more preferable that the through holes are arranged regularly in order to suppress variations in breathability and heat insulation.
[0084] The diameter of the through hole is preferably 100 μm or more and 2000 μm or less. By having the diameter of the through hole be preferably 100 μm or more, more preferably 200 μm or more, and even more preferably 300 μm or more, when a certain amount of ventilation is imparted to the laminate, the number of holes is not too large, and a laminate with excellent heat insulation can be obtained. In addition, by having the diameter of the through hole be preferably 2000 μm or less, more preferably 1000 μm or less, and even more preferably 800 μm or less, when a certain amount of ventilation is imparted to the laminate, the holes are dispersed, and the heat insulation can be prevented from decreasing.
[0085] The diameter of the through hole is measured by the following procedure. (i) Ten small samples (50 mm x 50 mm) are randomly taken from the laminate. (ii) Using a microscope (e.g., Keyence Corporation's "VW-9000") or a scanning electron microscope (SEM, e.g., Keyence Corporation's "VHX-D500"), photographs are taken at 10 to 50x magnification, showing 5 through-holes from each sample, for a total of 50 through-holes. (iii) The diameters of the through holes are measured, averaged, and rounded off to the first decimal place to determine the diameter of the through holes (μm). If the shape of the through holes is not a perfect circle, the diameter of a perfect circle with the same area as the holes is determined and this is the diameter of the through holes.
[0086] The aperture ratio of the through holes in the laminate is preferably 0.05% or more and 9.00% or less. By making the aperture ratio of the through holes preferably 0.05% or more, more preferably 0.10% or more, the laminate has excellent breathability, and the time required for decompression can be shortened when used as a heat insulating material. In addition, by making the aperture ratio of the through holes preferably 9.00% or less, more preferably 7.00% or less, and even more preferably 5.00% or less, the decrease in heat insulating properties can be prevented.
[0087] In addition, when the through holes are regularly arranged, the aperture ratio of the through holes is a value measured by the following procedure. However, "regularly arranged" here means that the interval between adjacent holes is constant or that the form includes a repeating pattern, and the other cases are referred to as "irregularly arranged through holes". (i) Ten small sample pieces (50 mm x 50 mm) are randomly taken from the laminate. (ii) Using a microscope (e.g., Keyence Corporation's "VW-9000") or a scanning electron microscope (SEM, e.g., Keyence Corporation's "VHX-D500"), take a total of 10 photographs at a magnification of 10 to 50 times, one from each sample, so that at least one repeating pattern of through holes is included in each photograph. However, if the distance between the through holes is long, it is not necessary for the repeating pattern to be included. (iii) From each photograph, the area of the through holes and the area of the smallest unit of the repeated pattern of through holes are calculated and averaged. Then, the aperture ratio (%) is calculated using the following formula and rounded off to the third decimal place. If the distance between the through holes is long, the distance between the through holes may be measured using a ruler. Opening rate (%)=(area of through hole)×(number of through holes contained in the smallest unit of the repeating pattern) / (area of the smallest unit of the repeating pattern)×100.
[0088] On the other hand, when the through holes are arranged irregularly, the aperture ratio of the through holes is a value measured by the following procedure. (i) Ten small sample pieces (50 mm x 50 mm) are randomly taken from the laminate. (ii) Using a microscope (e.g., Keyence Corporation's "VW-9000") or a scanning electron microscope (SEM, e.g., Keyence Corporation's "VHX-D500"), take a total of 10 photographs at a magnification of 10 to 50 times, one for each sample, so that at least one through-hole is included in each photograph. (iii) Calculate the area of the perforation from each photograph and average them. (iv) 10 samples (total area: 50 mm × 50 mm × 10 = 2500 mm 2 ) count the total number of through holes contained in the sample, calculate the aperture ratio using the following formula, average the average, and round off to the third decimal place. Opening rate (%) = (average area of through holes (mm 2 )) x (total number of through holes) / 2500mm 2 ×100.
[0089] In addition, in the laminate of the present invention, the ratio of the thickness of the fiber layer to the thickness of the thermoplastic resin layer (hereinafter, sometimes simply abbreviated as "thickness ratio") is preferably 5 or more and 40 or less. Here, when there are a plurality of the fiber layers and / or the thermoplastic resin layers, the thickness ratio refers to the ratio of the total thickness of all the fiber layers to the total thickness of all the thermoplastic resin layers. By the thickness ratio being preferably 5 or more, more preferably 6 or more, and even more preferably 7 or more, when a plurality of laminates are stacked and used as a thermal insulation material, the distance between the thermoplastic resins in the adjacent laminates is sufficiently secured to suppress heat conduction, and a laminate with excellent thermal insulation can be obtained. On the other hand, by the thickness ratio being preferably 40 or less, more preferably 35 or less, and more preferably 30 or less, the laminate retains flexibility and has excellent conformability to complex shapes when used as a thermal insulation material, which further improves the workability when used as a thermal insulation material, and since a larger number of laminates can be arranged in a given space, the thermal insulation can be improved.
[0090] Furthermore, the laminate of the present invention has an apparent density of 0.10 g / cm 3 More than 0.35g / cm 3 The lower limit of the apparent density range is 0.10 g / cm 3 More than 0.15 g / cm 3 By setting the apparent density to be equal to or greater than 0.35 g / cm3, the laminate has sufficient strength for practical use. 3 Less than 0.30 g / cm 3 , more preferably 0.25 g / cm 3 This suppresses thermal conduction and results in a laminate with excellent heat insulating properties.
[0091] In the present invention, the apparent density of the laminate refers to a value calculated by the following formula and rounded off to two decimal places: Apparent density (g / cm 3 )=Weight (g / m 2 ) ÷ thickness (μm) Here, the above-mentioned thickness refers to the thickness (μm) of the laminate obtained by (i) and (ii) of the measurement method for "fiber layer thickness", and the basis weight refers to the basis weight of the laminate measured and calculated by the method described below.
[0092] The mass per unit area of the laminate is 10 g / m 2 More than 60g / m 2 The mass per unit area is preferably 10 g / m or less. 2 More preferably, 15 g / m 2 More preferably, 20 g / m 2 By satisfying the above requirements, a laminate having sufficient strength for practical use can be obtained. On the other hand, the mass per unit area is preferably 60 g / m 2 Less than 50 g / m 2 More preferably, 40 g / m 2 By satisfying the above condition, the laminate can maintain flexibility and can conform to complex shapes when used as a thermal insulating material.
[0093] In the present invention, the mass per unit area (basis weight) of the laminate is determined in accordance with "6.2 Mass per unit area" of JIS L1913:2010 "Test methods for general nonwoven fabrics" and is measured by the following procedure. (i) Take three test pieces measuring 20 cm x 25 cm per metre of sample width. (ii) Weigh the mass (g) of each at standard conditions. (iii) The average value is 1 m 2 Mass per unit (g / m 2 )
[0094] The laminate has an air permeability of 1.0 cm 3 / (cm 2 sec) or more. The airflow rate is preferably 1.0 cm 3 / (cm 2 ·sec) or more, preferably 2.0 cm 3 / (cm 2sec) or more, more preferably 3.0 cm 3 / (cm 2 By setting the air permeability at 50.0 cm 3 or more, the time required for decompression can be shortened when the laminate is used as a heat insulating material. 3 / (cm 2 ·sec) or less, more preferably 40.0 cm 3 / (cm 2 sec) or less, and more preferably 30.0 cm 3 / (cm 2 By keeping the heat insulating property at 100° C. for 10 minutes or less, the entire laminate is densified, and when a plurality of laminates of the present invention are stacked and used as a heat insulating material, it is possible to prevent a decrease in the heat insulating property.
[0095] The air permeability of the laminate is measured in accordance with "6.8.1 Frazier type method" of JIS L1913:2010 "General nonwoven fabric test methods" by the following procedure. (1) Test pieces measuring 150 mm x 150 mm are taken from the laminate, three pieces per meter in the width direction. (2) Using a breathability tester (e.g., TEXTEST's "FX3300-IV"), measure the amount of air passing through each test piece (cm) at a barometer pressure of 125 Pa. 3 / (cm 2 Measure the time (seconds). (3) Average the measurement values of all test pieces and round off to the first decimal place.
[0096] The air permeability can be controlled by appropriately adjusting the average single fiber diameter, basis weight, apparent density, and / or the thermal bonding conditions (shape of the bonded part, compression rate, temperature, linear pressure, etc.) described below.
[0097] The laminate of the present invention is preferably in any one of the following embodiments. (Embodiment 1) The aforementioned laminate, wherein one of the outermost layers of the laminate is the aforementioned fiber layer, and the arithmetic mean roughness Ra of the outermost layer on the fiber layer side is 3.0 μm or more and 30.0 μm or less. (Embodiment 2) The aforementioned laminate, wherein one of the outermost layers of the laminate is the aforementioned thermoplastic resin layer, and the arithmetic mean roughness Ra of the outermost layer on the thermoplastic resin layer side is 0.01 μm or more and less than 3.00 μm. (Embodiment 3) The laminate, wherein one outermost layer of the laminate is the fiber layer, and the arithmetic mean roughness Ra of the outermost layer on the fiber layer side is 3.0 μm or more and 30.0 μm or less, and the other outermost layer of the laminate is the thermoplastic resin layer, and the arithmetic mean roughness Ra of the outermost layer on the thermoplastic resin layer side is 0.01 μm or more and less than 3.00 μm. These will be explained in further detail below.
[0098] (Embodiment 1) In this embodiment, first, one of the outermost layers of the laminate is the above-mentioned fiber layer. By doing so, when used as a thermal insulation material, a laminate having excellent thermal insulation performance due to the presence of voids between the fibers can be obtained.
[0099] Furthermore, in this case, the arithmetic mean roughness Ra of the outermost layer on the fiber layer side is preferably 3.0 μm or more and 30.0 μm or less. The lower limit of the range of the arithmetic mean roughness Ra is preferably 3.00 μm or more, more preferably 5.00 μm or more, and even more preferably 8.00 μm or more, so that when a plurality of laminates are stacked and used as a thermal insulation material, the contact area between the laminates can be reduced, and the thermal insulation performance can be further improved. On the other hand, the upper limit of the range of the arithmetic mean roughness Ra is preferably 30.00 μm or less, more preferably 25.00 μm or less, and even more preferably 20.00 μm or less, so that the average single fiber diameter is prevented from being extremely large and the apparent density is prevented from being extremely low, and the laminate can be made to maintain its strength.
[0100] In the present invention, the arithmetic mean roughness Ra of the outermost layer is to be a value measured as follows in accordance with "4.2.1 Arithmetic mean height of profile curve" of JIS B0601:2013 "Geometric product specification (GPS)-Surface quality: Profile curve method-Terminology, definitions and surface quality parameters" for not only the fiber layer side but also the thermoplastic resin side. (i) Test pieces measuring 100 mm x 100 mm are taken from the laminate at equal intervals across the width of the laminate, 10 pieces per meter. (ii) The test piece is set on the sample stage, and a surface roughness measuring instrument (such as the small surface roughness measuring instrument "SURFTEST SJ-210" manufactured by Mitutoyo Corporation) is used to measure the contour curves in the vertical direction (the lengthwise direction of the laminate, i.e., MD direction) and horizontal direction (the width direction of the laminate, i.e., CD direction) for the surface of the outermost layer of the laminate, and the arithmetic mean roughness Ra (μm) is calculated. However, the measurement should be performed so that the needle of the detector does not pass over the through hole during the measurement. (iii) Average the measurement values of all test pieces and round to the nearest tenth.
[0101] Furthermore, when one of the outermost layers of the laminate is the fiber layer, the average single fiber diameter of the fibers constituting the outermost fiber layer (hereinafter also referred to as the "first fiber layer") is preferably 6.0 μm or more and 30.0 μm or less. The lower limit of the average single fiber diameter range of the first fiber layer is preferably 6.0 μm or more, more preferably 8.0 μm or more, even more preferably 10.0 μm or more, and particularly preferably 12.0 μm or more, so that the number of fibers per unit area is reduced, and when a plurality of laminates are stacked and used as a thermal insulation material, the contact area between the laminates can be reduced. In addition, the voids inside the fiber layer can be expanded, so that the laminate can be given appropriate breathability. On the other hand, by having the average single fiber diameter of the fibers of the first fiber layer be preferably 30.0 μm or less, more preferably 26.0 μm or less, even more preferably 22.0 μm or less, and particularly preferably 18.0 μm or less, the uniformity of the fiber layer can be improved, and therefore, when used as a thermal insulation material, a laminate with uniform thermal insulation performance can be obtained.
[0102] The average single fiber diameter (μm) of the fibers in the first fiber layer is calculated by the following procedure. (i) Ten small samples (100 x 100 mm) are randomly taken from the laminate. (ii) A surface photograph of the first fiber layer is taken at 1000 to 5000 times magnification using a microscope (e.g., Keyence's "VW-9000") or a scanning electron microscope (e.g., Keyence's "VHX-D500"). The width (diameter) of 10 fibers from each sample, totaling 100 fibers, is measured. Note that measurements are taken while avoiding areas where the fibers have been crushed by thermal compression bonding or the like, which will be described later. In addition, if the cross section of the fiber is irregular, the cross-sectional area of the fiber is measured from the cross-sectional photograph, and the diameter of a perfect circle having the same cross-sectional area is determined. (iii) Average the diameters of the 100 measured values and round to the nearest tenth.
[0103] In this embodiment, in order to improve the uniformity of the laminate of the present invention or to improve the adhesion between the first fiber layer and the thermoplastic resin layer, it is also a preferred embodiment to provide another fiber layer (hereinafter referred to as a second fiber layer) between the first fiber layer and the thermoplastic resin layer, the fiber layer being composed of fibers having a finer fiber diameter than the fibers of the first fiber layer.
[0104] When a nonwoven fabric is used as a preferred embodiment of the first fibrous layer, the nonwoven fabric constituting the second fibrous layer is preferably a melt-blown nonwoven fabric obtained by a melt-blowing method, since it has excellent productivity and uniformity.
[0105] The average single fiber diameter of the fibers constituting this second fiber layer is preferably 0.1 μm or more and less than 6.0 μm. By having the average single fiber diameter of the fibers be preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and particularly preferably 0.7 μm or more, a laminate having excellent productivity and moderate breathability can be obtained. On the other hand, by having the average single fiber diameter of the fibers be preferably less than 6.0 μm, more preferably 5.0 μm or less, even more preferably 4.0 μm or less, and particularly preferably 3.0 μm or less, the uniformity of the laminate can be improved and the reduction in the reflectivity of radiant heat caused by the generation of unevenness on the surface of the thermoplastic resin layer can be prevented.
[0106] The average single fiber diameter (μm) of the fibers constituting the nonwoven fabric of the second fiber layer is to be calculated in the same manner as for the average single fiber diameter (μm) of the fibers of the first fiber layer after peeling off the first fiber layer and / or the thermoplastic resin layer from the laminate of the present invention.
[0107] (Embodiment 2) In this embodiment, first, one of the outermost layers of the laminate is the thermoplastic resin layer, whereby a laminate having excellent radiant heat reflectivity can be obtained.
[0108] Furthermore, in this case, the arithmetic mean roughness Ra of the outermost layer on the thermoplastic resin layer side is preferably 0.01 μm or more and less than 3.00 μm. By making the arithmetic mean roughness Ra preferably 3.00 μm or less, more preferably 2.00 μm or less, and even more preferably 1.00 μm or less, the surface area of the thermoplastic resin layer is reduced, improving the covering efficiency of the metal layer described below, and resulting in a laminate with excellent radiant heat reflectivity. On the other hand, by making the arithmetic mean roughness Ra preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.10 μm or more, when a plurality of the laminates are stacked and used as a heat insulating material, the contact area between the laminates is reduced, resulting in a laminate with excellent heat insulating properties.
[0109] Furthermore, it is preferable that the outermost thermoplastic resin layer is a thermoplastic resin layer the surface of which is covered with a metal layer, thereby resulting in a laminate having excellent radiant heat reflectivity.
[0110] (Embodiment 3) This embodiment is an embodiment in which embodiment 1 and embodiment 2 are carried out simultaneously.
[0111] Furthermore, in this case, it is preferable that the ratio of the arithmetic mean roughness Ra of the outermost layer on the fiber layer side to the arithmetic mean roughness Ra of the outermost layer on the thermoplastic resin layer side is 2 or more and less than 3000. This results in a laminate that is excellent in heat insulation and excellent in reflecting radiant heat when a plurality of the laminates are stacked together and used as a heat insulating material.
[0112] [Method of manufacturing laminate] A preferred embodiment of the method for producing the laminate of the present invention will now be described.
[0113] (Formation of fiber layer) Here, a specific description will be given by taking as an example a method for forming a fiber layer in the case where the fiber layer is a spunbond nonwoven fabric layer.
[0114] The spunbond nonwoven fabric layer is a layer of long-fiber nonwoven fabric produced by the spunbond method, which is excellent in productivity and mechanical strength, and can also suppress the fuzzing and fiber shedding that tend to occur in short-fiber nonwoven fabrics.
[0115] In the spunbond method, a thermoplastic resin is first melted in an extruder, metered, and fed to a spinneret, and spun into long fibers. The spinning temperature when melting and spinning the thermoplastic resin is preferably (Tm+20)°C to (Tm+90)°C, more preferably (Tm+30)°C to (Tm+80)°C, and even more preferably (Tm+40)°C to (Tm+70)°C, where Tm is the melting point of the thermoplastic resin (°C). This makes it possible to obtain a stable molten state and excellent spinning stability.
[0116] Next, the spun long fibers are sucked by an ejector. The shapes of the spinneret and the ejector are not particularly limited, and various shapes such as a round shape and a rectangular shape can be adopted. Among them, a combination of a rectangular spinneret and a rectangular ejector is preferably used because it uses a relatively small amount of compressed air, is excellent in energy cost, is less likely to cause fusion or abrasion between the yarns, and is easy to open the yarns.
[0117] The spun long fiber yarn is then cooled. Examples of methods for cooling the spun yarn include a method of forcibly blowing cold air onto the yarn, a method of naturally cooling the yarn at the ambient temperature around the yarn, and a method of adjusting the distance between the spinneret and the ejector. A combination of these methods can also be used. The cooling conditions can be selected taking into consideration the discharge rate per hole of the spinneret, the spinning temperature, the ambient temperature, and the like.
[0118] Furthermore, the cooled and solidified yarn is pulled and stretched by compressed air ejected from an ejector.
[0119] The spinning speed is preferably 3000 m / min to 6000 m / min, more preferably 3500 m / min to 5500 m / min, and further preferably 4000 m / min to 5000 m / min. By setting the spinning speed at 3000 m / min to 6000 m / min, high productivity is achieved, and the orientation and crystallization of the fibers is promoted, making it possible to obtain long fibers with high strength.
[0120] The drawn filaments are then collected on a moving net to obtain a nonwoven fibrous web.
[0121] It is also preferable to temporarily bond the nonwoven fiber web by contacting one side of the nonwoven fiber web with a hot flat roll on a net. In this way, it is possible to prevent the surface layer of the nonwoven fiber web from turning over or being blown away while being transported on the net, which would cause deterioration of the formation, and to improve the transportability from collecting the yarns to thermocompression bonding.
[0122] In addition, the resulting nonwoven fiber web can be fused to form fused portions to obtain a desired spunbonded nonwoven fabric layer.
[0123] The method for fusing the nonwoven fiber web is not particularly limited, and examples thereof include a method of heat fusing using various rolls such as a heat embossing roll having engravings (uneven portions) on the surface of a pair of upper and lower rolls, a heat embossing roll consisting of a combination of a roll with one flat (smooth) surface and a roll with engravings (uneven portions) on the surface of the other roll, and a heat calendar roll consisting of a combination of a pair of upper and lower flat (smooth) rolls; a method of heat fusing using ultrasonic vibrations of a horn; and a method of passing hot air through the nonwoven fiber web to soften or melt the surface of the core-sheath type composite fibers and heat fusing the fiber intersections.
[0124] Among them, it is preferable to use a heat embossing roll having engraved (uneven portions) on the surface of a pair of upper and lower rolls, or a heat embossing roll consisting of a combination of a roll with one flat (smooth) surface and a roll with engraved (uneven portions) on the surface of the other roll. In this way, it is possible to provide, with good productivity, fused portions that improve the strength of the spunbonded nonwoven fabric layer and non-fused portions that improve flexibility and breathability.
[0125] As for the surface material of the hot embossing roll, it is preferable to use a pair of metal rolls in order to obtain a sufficient thermocompression effect and to prevent the engraving (convex and concave portions) of one embossing roll from being transferred to the surface of the other roll.
[0126] The embossed adhesion area ratio by such a hot embossing roll is preferably 5 to 30 area %. By setting the adhesion area to preferably 5 area % or more, more preferably 8 area % or more, and even more preferably 10 area % or more, it is possible to obtain a strength suitable for practical use. On the other hand, by setting the adhesion area to preferably 30 area % or less, more preferably 25 area % or less, and even more preferably 20 area % or less, it is possible to prevent the flexibility and softness from being impaired. Even when ultrasonic bonding is used, it is preferable that the adhesion area ratio is in the same range.
[0127] The adhesive area referred to here means the ratio of the adhesive area to the entire spunbonded nonwoven fabric layer. Specifically, in the case of thermal bonding using a pair of uneven rolls, it means the ratio of the part (adhesive part) where the convex part of the upper roll and the convex part of the lower roll overlap and contact the nonwoven fiber web to the entire spunbonded nonwoven fabric layer. In addition, in the case of thermal bonding using an uneven roll and a flat roll, it means the ratio of the part (adhesive part) where the convex part of the uneven roll contacts the nonwoven fiber web to the entire spunbonded nonwoven fabric layer. In addition, in the case of ultrasonic bonding, it means the ratio of the part (adhesive part) that is thermally fused by ultrasonic processing to the entire spunbonded nonwoven fabric layer. When sufficient heat is applied to the adhesive part during thermal bonding and all the fibers in the adhesive part are fused, the adhesive part and the fused part can be considered to have the same area.
[0128] The shape of the bonded portion by the hot embossing roll or ultrasonic bonding is not particularly limited, but for example, a circle, an ellipse, a square, a rectangle, a parallelogram, a rhombus, a regular hexagon, a regular octagon, etc. can be used. In addition, it is preferable that the bonded portions are uniformly present at regular intervals in the longitudinal direction (transport direction) and the width direction of the spunbonded nonwoven fabric layer. In this way, the variation in strength of the spunbonded nonwoven fabric layer can be reduced.
[0129] The surface temperature of the hot embossing roll during thermal bonding is preferably (Tm-30)°C to (Tm+10)°C, where Tm (°C) is the melting point of the thermoplastic resin used. By setting the surface temperature of the hot roll to preferably (Tm-30)°C or higher, more preferably (Tm-20)°C or higher, and even more preferably (Tm-10)°C or higher, it is possible to obtain a spunbonded nonwoven fabric layer with a strength that can be used in practical applications by firmly thermal bonding. In addition, by setting the surface temperature of the hot embossing roll to preferably (Tm+10)°C or lower, more preferably (Tm+5)°C or lower, and even more preferably Tm (°C) or lower, it is possible to suppress excessive thermal bonding, obtain a spunbonded nonwoven fabric layer with excellent strength and flexibility, and prevent the trouble of the nonwoven fiber web wrapping around the hot embossing roll.
[0130] The line pressure of the hot embossing roll during thermal bonding is preferably 50 N / cm to 500 N / cm. By setting the line pressure of the roll to preferably 50 N / cm or more, more preferably 100 N / cm or more, and even more preferably 150 N / cm or more, it is possible to obtain a spunbonded nonwoven fabric layer with a strength that can be used practically by firmly thermal bonding. On the other hand, by setting the line pressure of the hot embossing roll to preferably 500 N / cm or less, more preferably 400 N / cm or less, and even more preferably 300 N / cm or less, it is possible to suppress excessive bonding and obtain a spunbonded nonwoven fabric layer with excellent strength and flexibility.
[0131] In addition, by laminating the collected spunbond nonwoven fiber web or heat-bonded spunbond nonwoven fabric layers in two, three or four layers, productivity and uniformity of the fabric can be improved. In the laminate according to the present invention, when a plurality of spunbond nonwoven fabric layers are continuously laminated, these spunbond nonwoven fabric layers are regarded as one spunbond nonwoven fabric layer.
[0132] In the present invention, for the purpose of adjusting the thickness of the spunbonded nonwoven fabric layer, thermal compression bonding can be performed using a thermal calendar roll consisting of a pair of upper and lower flat rolls before and / or after thermal bonding using the above-mentioned hot embossing roll. The pair of upper and lower flat rolls refers to metal rolls or elastic rolls with no irregularities on the roll surfaces, and a pair of metal rolls or a pair of metal rolls and elastic rolls can be used.
[0133] The elastic roll here refers to a roll made of a material having elasticity compared to a metal roll. Examples of the elastic roll include so-called paper rolls such as paper, cotton, and aramid paper, and resin rolls made of urethane resin, epoxy resin, silicon resin, polyester resin, hard rubber, and mixtures of these resins.
[0134] Next, as a preferred embodiment of the present invention, a production method in which the first fiber layer is the above-mentioned spunbonded nonwoven fabric layer and the second fiber layer is a meltblown nonwoven fabric layer will be specifically described.
[0135] The melt-blown nonwoven fabric layer is a long-fiber nonwoven fabric produced by the melt-blowing method, which is highly productive and can easily produce fine fibers on the order of several microns.
[0136] In the melt-blowing method, molten thermoplastic resin is extruded from a spinneret to form threads. Heated air or the like (hereinafter, simply referred to as hot air) is sprayed from a certain angle onto the extruded threads to reduce their diameter, and the threads are then deposited in a collection section to form a melt-blown nonwoven fabric layer.
[0137] In the present invention, the thermoplastic resin is melted in an extruder, metered, and fed to a spinneret to be spun into long fibers. The spinning temperature when melting and spinning the thermoplastic resin is preferably (Tm+40)°C to (Tm+160)°C, more preferably (Tm+60)°C to (Tm+140)°C, and even more preferably (Tm+80)°C to (Tm+120)°C, where Tm is the melting point of the thermoplastic resin (°C). This allows the fibers to be uniformly thinned in diameter by achieving a stable molten state.
[0138] The temperature of the hot air blown onto the yarn immediately after it is discharged is preferably (Tm+50)° C. to (Tm+170)° C., more preferably (Tm+70)° C. to (Tm+150)° C., and even more preferably (Tm+90)° C. to (Tm+130)° C., where Tm is the melting point of the thermoplastic resin (° C.). This makes it possible to achieve a stable molten state and uniformly reduce the diameter of the fibers.
[0139] The angle at which the hot air is blown onto the yarn immediately after it is discharged is preferably 30° to 45° with respect to the traveling direction of the yarn, which allows the fibers to be uniformly thinned.
[0140] Methods for bonding the spunbond nonwoven fabric, which is the first fiber layer, and the meltblown nonwoven fabric, which is the second fiber layer, can be used to thermally laminate the two layers directly or using a binder resin or hot melt resin, or a method for bonding them using a rubber-based adhesive or other adhesive.
[0141] Also, a meltblown nonwoven web can be collected directly on the spunbonded nonwoven fiber web collected by the above-mentioned manufacturing method, or on a spunbonded nonwoven fabric layer obtained by forming fused parts on the spunbonded nonwoven fiber web. By doing so, the process of laminating the spunbonded nonwoven fabric layer (first fiber layer) and the meltblown nonwoven fabric layer (second fiber layer) later can be omitted, and the manufacturing process can be simplified.
[0142] (Formation of thermoplastic resin layer, formation of laminate) Here, as a preferred embodiment of the laminate, a production method in which the thermoplastic resin layer is a film or an extrusion laminate whose surface is covered with a metal layer will be specifically described.
[0143] In the laminate of the present invention, when laminating the fiber layer and the thermoplastic resin layer, it is preferable to include a step of heat-sealing the fiber layer and the thermoplastic resin layer.
[0144] The method of heat-sealing the fiber layer and the thermoplastic resin layer may include a method of heat-sealing the fiber layer and the thermoplastic resin layer by penetrating them with a heated protrusion, a method of heat-sealing the fiber layer and the thermoplastic resin layer by stacking them and heating them while applying pressure, a method of heat-sealing the fiber layer and the thermoplastic resin layer by sandwiching a binder resin or a hot melt resin between them and heating them, and a method of extrusion laminating the fiber layer and the thermoplastic resin layer using a thermoplastic resin with a low melting point. Among them, the method of heat-sealing the fiber layer and the thermoplastic resin layer by penetrating them with a heated protrusion is preferable because it omits the step of opening a through hole after lamination, simplifies the manufacturing process, and suppresses the generation of volatile substances in a vacuum or low pressure environment in which the laminate is used as a heat insulating material.
[0145] When using a method of thermally fusing the fiber layer and the thermoplastic resin layer by penetrating the layer with a heated protrusion, it is preferable that the diameter of the resulting through hole is 100 μm or more and 2000 μm or less, and the aperture ratio of the through hole is 0.05% or more and 9.00% or less. By setting the aperture ratio of the through hole to preferably 0.05% or more, more preferably 0.10% or more, and the diameter of the through hole to preferably 2000 μm or less, more preferably 1000 μm or less, and even more preferably 800 μm or less, an appropriate number of bonding points can be maintained and the occurrence of wrinkles during bonding can be suppressed.
[0146] As a method for laminating the fiber layer and the thermoplastic resin layer, in addition to a method of heat fusion, a method of bonding them together using a rubber-based adhesive or the like can be used.
[0147] In the case where the fiber layer and the thermoplastic resin layer do not have through holes at the stage of laminating the fiber layer and the thermoplastic resin layer, a step of opening through holes after lamination is included. As a method for opening through holes, a method of opening through holes by penetrating a projection at room temperature or heated, a method of opening through holes by using a laser or the like, or the like can be adopted.
[0148] The binder resin sandwiched between the fiber layer and the thermoplastic resin layer is not particularly limited, but is preferably a resin mainly composed of an organic component, such as polyester resin, polyurethane resin, acrylic resin, methacrylic resin, polyamide resin, polyethylene resin, polypropylene resin, polyvinyl chloride resin, polyvinylidene chloride resin, polystyrene resin, polyvinyl acetate resin, fluorine-based resin, epoxy resin, ionomer resin, and silicone resin. These resins may be used alone, or may be copolymers or mixtures of two or more kinds. The rubber-based adhesive sandwiched between the fiber layer and the thermoplastic resin layer is not particularly limited, but may be synthetic rubber such as styrene-butadiene rubber, chloroprene rubber, and nitrile rubber, or natural rubber such as isoprene rubber. Double-sided tapes or adhesive sheets having the binder resin or the rubber-based adhesive on both sides of the support may be used. The binder resin and rubber-based adhesive are preferably those that generate little volatile substances in a vacuum or low-pressure environment in which the laminate is used as a heat insulating material.
[0149] The amount of binder resin or hot melt resin attached per unit area is 0.1 g / m 2 More than 10g / m 2 The amount of adhesion per unit area is preferably 0.1 g / m or less. 2 More preferably, 0.5 g / m 2 More preferably, 1.0 g / m 2By setting the amount to 10.0 g / m or more, the fiber layer and the thermoplastic resin layer can be firmly thermally bonded to each other. In addition, the amount of adhesion per unit area is preferably 10.0 g / m or more. 2 Less than 5.0 g / m 2 Less than 3.0 g / m, more preferably 3.0 g / m 2 By setting the above, it is possible to prevent the molten binder resin or hot melt resin from seeping out from the surface of the fiber layer or the thermoplastic resin layer, to prevent the flexibility of the laminate from being impaired, and to suppress the occurrence of wrinkles.
[0150] The temperature for thermal lamination is preferably (Tma-10)°C to (Tma+30)°C, where Tma (°C) is the melting point of the binder resin or hot melt resin used. By setting the temperature for thermal lamination to preferably (Tma-10)°C or higher, more preferably (Tma-5)°C or higher, and even more preferably Tma (°C) or higher, the fiber layer and the thermoplastic resin layer can be firmly thermally bonded. By setting the temperature for thermal lamination to preferably (Tma+30)°C or lower, more preferably (Tma+25)°C or lower, and even more preferably (Tma+20)°C or lower, it is possible to prevent the molten binder resin or hot melt resin from seeping out from the surface of the fiber layer or the thermoplastic resin layer, and to prevent the fiber layer or the thermoplastic resin layer from being deteriorated by heat.
[0151] In addition, the resin can be directly extrusion laminated onto the fiber layer to obtain a configuration similar to that obtained when the film is used. By directly extrusion laminating the resin onto the fiber layer, the occurrence of wrinkles can be suppressed. By directly extrusion laminating the resin onto the fiber layer, the occurrence of wrinkles can be suppressed.
[0152] Next, as a method for covering the surface of the thermoplastic resin layer with a metal layer, a method for depositing a metal or metal oxide can be used. As the deposition method, physical deposition methods such as vacuum deposition, EB deposition, sputtering, and ion plating, and chemical deposition methods such as plasma CVD can be used. Among them, the vacuum deposition method or the sputtering method is preferably used from the viewpoint of productivity. The deposition of a metal or metal oxide on the surface of the thermoplastic resin layer may be performed before lamination with the fiber layer, or after lamination with the fiber layer. In addition, when the deposition is performed before lamination with the fiber layer, the deposition may be performed on one side or both sides of the thermoplastic resin layer.
[0153] When forming the metal layer by vapor deposition, it is preferable to subject the surface to be vapor-deposited to a pretreatment such as a corona discharge treatment in order to improve the adhesion of the metal film.
[0154] After the metal layer is formed, it is preferable to perform a heat treatment at 100° C. or more. This can increase the affinity between the fiber surface and the metal layer, and can prevent the metal layer from cracking or peeling during use.
[0155] Here, when there are multiple fiber layers and / or multiple thermoplastic resin layers, they are laminated so that the ratio of the total thickness of all fiber layers to the total thickness of all thermoplastic resin layers is 5 or more and 40 or less.
[0156] The laminate of the present invention has high reflectivity of radiant heat, excellent heat insulation and breathability, and excellent workability, and therefore can be widely used in sanitary materials, medical materials, daily materials, industrial materials, etc. In particular, in daily materials and industrial materials, it can be suitably used as a heat insulating material used in a vacuum or low pressure environment. That is, the heat insulating material of the present invention uses the laminate of the present invention.
[0157] When the laminate of the present invention is used as a heat insulating material, it is preferable to use a plurality of laminates in order to improve the performance. The laminates may be used by stacking a plurality of sheets without bonding, or may be used by bonding a plurality of sheets of the laminate. In this case, the laminates may be stacked so that the fiber layers are in contact with each other, the thermoplastic resin layers are in contact with each other, or the fiber layer and the thermoplastic resin layer are in contact with each other.
[0158] The heat insulating material of the present invention has high reflectivity of radiant heat, excellent heat insulating properties, and excellent breathability, which allows easy evacuation and pressure reduction, and excellent workability, and therefore can be suitably used for vacuum insulated containers. That is, the vacuum insulated container of the present invention is made using the heat insulating material of the present invention. EXAMPLES
[0159] Next, the laminate of the present invention will be specifically described based on examples, although the present invention is not limited to only these examples.
[0160] [Measurement method] The evaluation methods and measurement conditions used in the examples are described below. Unless otherwise specified, the measurements of each physical property were performed according to the above-mentioned methods.
[0161] (1) Average single fiber diameter (μm) of the fibers constituting the fiber layer The average single fiber diameter of the fibers constituting the fiber layer was measured and calculated by the above-mentioned method using a scanning electron microscope (SEM) "VHX-D500" manufactured by Keyence Corporation.
[0162] (2) Weight of the fiber layer, thermoplastic resin layer, and laminate (g / m 2 ) The basis weight of each fiber was measured and calculated by the above-mentioned method.
[0163] (3) Thickness of fiber layer, thermoplastic resin layer, and laminate (μm), ratio of fiber layer thickness to thermoplastic resin layer thickness (-) The thicknesses of the layers were measured and calculated by the above-mentioned method using a pressure tool "SM-114" manufactured by Techclock Corporation and a scanning electron microscope (SEM) "VHX-D500" manufactured by Keyence Corporation. The ratio of the thickness of the fiber layer to the thickness of the thermoplastic resin layer (simply referred to as "thickness ratio" in Tables 1 and 2) was measured and calculated by the above-mentioned method.
[0164] (4) Apparent density (g / cm3) of the fiber layer, thermoplastic resin layer, and laminate 3 ) The apparent density of each was measured and calculated by the above-mentioned method.
[0165] (5) Arithmetic mean roughness Ra (μm) of the surfaces of the fiber layer, thermoplastic resin layer, and laminate The arithmetic mean roughness Ra was measured and calculated using a surface roughness measuring instrument "SURFTEST" SJ-210 manufactured by Mitutoyo Corporation according to the above-mentioned method.
[0166] (6) Metal layer thickness (nm) The thickness of the metal layer was measured and calculated by the above-mentioned method using a transmission electron microscope (TEM) "JEM-F200" manufactured by JEOL Ltd.
[0167] (7) Hole diameter (μm) and aperture ratio (%) of the through hole The diameter of the through holes and the aperture ratio of the through holes were measured and calculated by the above-mentioned methods using a scanning electron microscope (SEM) "VHX-D500" manufactured by Keyence Corporation.
[0168] (8) Air permeability of laminate (cm 3 / (cm 2 ·Seconds)) The air permeability was measured and calculated using a ventilation tester (TEXTEST Frazier type "FX3300-IV") according to the above-mentioned method. The air permeability of the laminate was 1.0 cm 3 / (cm 2 On the other hand, the ventilation rate was 0.05 cm 3 / (cm2 If the measured value was less than s, it was considered to be “unmeasurable.”
[0169] (9) Infrared light reflectance (%) The following infrared light reflectance was measured to evaluate the reflectivity of the laminate against radiant heat. First, three test pieces of 30 mm x 30 mm were taken from the laminate, and a gold-coated infrared integrating sphere detector (PIKE Technologies' Mid-IR IntegratIR Upward and DTGS detector) was attached to a Fourier transform infrared spectrophotometer (BRUKER's Tensor II), the inside of the integrating sphere was purged with nitrogen, and the infrared light reflectance was measured. The measurement wavelength was 5 μm to 25 μm, data was measured every 0.02 μm, and the reflectance at a wavelength of 20 μm was calculated from the measurement data. The reflectance of the three test pieces was averaged and rounded off to the first decimal place to obtain the infrared light reflectance (%). The reflectance was calculated as a relative reflectance when the reflectance of the gold-coated reflector was set to 100%. An infrared light reflectance of 60% or more was considered to pass.
[0170] (10) Decompression time (min), temperature rise (°C) The workability of the laminate was evaluated by measuring the decompression time (the time required to decompress the vacuum insulated container), and the heat insulating performance was evaluated by measuring the temperature rise. First, using a simple insulation tester (internal volume 1 L) equipped with a vacuum-capable insulation layer, 10 laminates were inserted into the insulation layer, and the insulation layer was depressurized by a vacuum pump through the laminates. -4 The time required to reach a vacuum level of 0.1 Pa or less was measured in minutes (rounded up to the nearest whole number) and recorded as the decompression time (minutes). A decompression time of 60 minutes or less was considered to be acceptable. If the above vacuum level was not reached within 180 minutes, it was deemed to be "unable to decompress." Next, the vacuum line of the insulation layer was sealed, and the simple insulation tester was left in a room controlled at room temperature of 25°C. Next, after confirming that the temperature difference between the inside and outside of the tester was 0.1°C or less, the tester was placed in a thermo-hygrostat chamber at a temperature of 75°C and a humidity of 50%RH. The temperature inside the tester was measured one hour after the insertion, and the temperature difference before and after the insertion was calculated, and the temperature rise (°C) was calculated by rounding off to the first decimal place. A temperature rise of 10°C or less was considered to be acceptable.
[0171] [Fiber layer] The nonwoven fabrics used as fiber layers in the examples and comparative examples were produced by the following method.
[0172] <Non-woven fabric N1> A homopolymer polypropylene (PP) resin with a melt flow rate (MFR) of 200 g / 10 min and a melting point of 163 ° C was melted in an extruder and spun from a spinneret with a hole diameter φ of 0.40 mm, a hole depth of 0.80 mm, and 2000 holes per 1 m in the width direction at a spinning temperature of 235 ° C and a single hole output rate of 0.40 g / min. After cooling and solidifying the spun thread, it was pulled and stretched by compressed air in an ejector and collected on a moving net to form a spunbond nonwoven fiber web made of polypropylene-based long fibers. The formed nonwoven fiber web was then thermally bonded using a pair of upper and lower heat embossing rolls consisting of the following upper and lower rolls under the conditions of a line pressure of 500 N / cm and a thermal bonding temperature of 150 ° C to obtain a spunbond nonwoven fabric. Upper roll: Metal embossed roll with polka dot pattern engraved on it, with an adhesive area rate of 11% Bottom roll: Metal flat roll The average single fiber diameter of this spunbond nonwoven fabric is 12.4 μm and the basis weight is 15 g / m 2 , and the thickness was 140 μm.
[0173] <Non-woven fabric N2> Weight is 30g / m 2 A spunbond nonwoven fabric was obtained in the same manner as for nonwoven fabric N1, except that the thickness was 210 μm.
[0174] <Non-woven fabric N3> Weight is 10g / m 2 A spunbond nonwoven fabric was obtained in the same manner as for nonwoven fabric N1, except that the thickness was 80 μm.
[0175] <Nonwoven fabric N4> A melt-blown nonwoven fabric was obtained using a polypropylene resin made of a homopolymer with a melt flow rate (MFR) of 1100 g / 10 min and a melting point of 163°C, a spinneret with a hole diameter of 0.20 mm, a hole depth of 2.4 mm, and 1000 holes per 1 m in the width direction, under conditions of a spinning temperature of 260°C, a hot air temperature of 265°C, and a single hole output rate of 0.10 g / min. The average single fiber diameter of this melt-blown nonwoven fabric was 1.0 μm, and the basis weight was 5 g / m. 2 , and the thickness was 20 μm.
[0176] <Non-woven fabric N5> Weight is 10g / m 2 A spunbond nonwoven fabric was obtained in the same manner as in nonwoven fabric N1, except that the thickness was 100 μm.
[0177] <Non-woven fabric N6> The nonwoven fabric N1 was further heat-bonded using a pair of upper and lower heat calendar rolls consisting of an upper roll and a lower roll under the conditions of a line pressure of 200 N / cm and a heat bonding temperature of 120° C. The average single fiber diameter of this spunbond nonwoven fabric was 12.4 μm and the basis weight was 15 g / m 2 , and the thickness was 80 μm.
[0178] <Non-woven fabric N7> A polyethylene terephthalate (PET) resin consisting of a homopolymer with an intrinsic viscosity (IV) of 0.65 and a melting point of 260°C was melted in an extruder and spun from a spinneret with a hole diameter φ of 0.40 mm, a hole depth of 0.80 mm, and 2000 holes per 1 m in the width direction at a spinning temperature of 290°C and a single hole output rate of 0.55 g / min. After cooling and solidifying the spun thread, it was pulled and stretched by compressed air in an ejector and collected on a moving net to form a spunbond nonwoven fiber web consisting of polyester-based long fibers. The formed nonwoven fiber web was then thermally bonded using a pair of upper and lower heat embossing rolls consisting of the following upper and lower rolls under the conditions of a line pressure of 500 N / cm and a thermal bonding temperature of 190°C to obtain a spunbond nonwoven fabric. Upper roll: Metal embossed roll with polka dot pattern engraved on it, with an adhesive area rate of 11% Bottom roll: metal flat roll. The average single fiber diameter of this spunbond nonwoven fabric is 13.0 μm and the basis weight is 15 g / m 2 , and the thickness was 80 μm.
[0179] <Non-woven fabric N8> A wet-laid nonwoven fabric made from polyethylene terephthalate (PET) was used. The average fiber diameter of this wet-laid nonwoven fabric was 7.4 μm, the average fiber length was 6.8 mm, and the basis weight was 15 g / m 2 , and the thickness was 50 μm.
[0180] [Thermoplastic resin layer] The films used as the base film of the thermoplastic resin layer in the examples and comparative examples were produced by the following method.
[0181] <Film F1> Made of polypropylene (PP) resin, with a basis weight of 14g / m 2 A film having a thickness of 15 μm was used.
[0182] <Film F2> Made of polypropylene (PP) resin, with a basis weight of 6g / m 2 A film with a thickness of 6 μm was used.
[0183] <Film F3> Made of polypropylene (PP) resin, with a basis weight of 18g / m 2 A film having a thickness of 20 μm was used.
[0184] <Film F4> Made of polyethylene terephthalate (PET) resin, with a basis weight of 28g / m 2 A film having a thickness of 20 μm was used.
[0185] <Film F5> Made of polyethylene terephthalate (PET) resin, with a basis weight of 21g / m 2 A film having a thickness of 15 μm was used.
[0186] [Example 1] A nonwoven fabric N1 was used as the fiber layer, and a film F1 was used as the base film for the thermoplastic resin layer. A powdered hot melt adhesive made of a polyethylene resin with a melting point of 105°C was used for adhesion. Next, a heated hot needle was used to create a hole diameter of 800 μm and a number of holes of 2500 pcs / m. 2 Through holes were opened so that the thickness of the laminate was 100 nm. Then, aluminum was vapor-deposited on the surface on which the film F1 was placed, and the surface of the film F1 was covered with an aluminum layer (metal layer) having a thickness of 100 nm. At this time, the thickness of the thermoplastic resin layer was 15 μm. No wrinkles were observed in the laminate. The evaluation results of the obtained laminate are shown in Table 1.
[0187] [Example 2] A laminate was obtained in the same manner as in Example 1, except that nonwoven fabric N2 was used as the fiber layer and film F2 was used as the base film of the thermoplastic resin layer. At this time, the thickness of the thermoplastic resin layer was 6 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 1.
[0188] [Example 3] The nonwoven fabric N3 and the nonwoven fabric N4 were bonded with a powdered hot melt adhesive made of a polyethylene resin having a melting point of 105°C to obtain a laminated nonwoven fabric. This laminated nonwoven fabric was used as a fiber layer, and the film F3 was attached to the nonwoven fabric N4 side as a base film for the thermoplastic resin layer. Otherwise, a laminate was obtained in the same manner as in Example 1. At this time, the thickness of the thermoplastic resin layer was 20 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 1.
[0189] [Example 4] Through-hole diameter 3000μm, number of holes 200 / m 2 A laminate was obtained in the same manner as in Example 1, except that the thickness of the thermoplastic resin layer was 15 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 1.
[0190] [Example 5] Through-hole diameter 800μm, number of holes 20,000 / m 2 A laminate was obtained in the same manner as in Example 1, except that the thickness of the thermoplastic resin layer was 15 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 1.
[0191] [Example 6] Through-hole diameter: 800μm, number of holes: 200,000 / m 2 A laminate was obtained in the same manner as in Example 1, except that the thickness of the thermoplastic resin layer was 15 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 1.
[0192] [Example 7] The fiber layer was made of nonwoven fabric N5, and the thermoplastic resin layer was made of film F1 as a base film. A powdered hot melt adhesive made of polyethylene resin with a melting point of 105°C was used for adhesion.
[0193] Next, aluminum was vapor-deposited onto the surface on which the film F1 was placed, so that the surface of the film F1 was covered with an aluminum layer (metal layer) having a thickness of 100 nm. At this time, the thickness of the thermoplastic resin layer was 15 μm.
[0194] Next, the surface of the side on which the film F1, which was covered with an aluminum layer (metal layer), was placed was adhered to a separately prepared nonwoven fabric N5. For adhesion, a powdered hot melt adhesive made of a polyethylene resin with a melting point of 105°C was used.
[0195] Next, a heated needle was used to create a hole with a diameter of 800 μm and a number of holes of 2500 / m. 2 The through holes were opened so that the thickness of the laminate was 1 / 100. No wrinkles were observed in the laminate. The laminate was evaluated and the results are shown in Table 1.
[0196] [Table 1] [Comparative Example 1] Except for not forming through holes, a laminate was obtained in the same manner as in Example 1. At this time, the thickness of the thermoplastic resin layer was 15 μm. No wrinkles were observed in the laminate. The laminate was evaluated and the results are shown in Table 2.
[0197] [Comparative Example 2] A laminate was obtained in the same manner as in Example 1, except that nonwoven fabric N6 was used as the fiber layer and film F3 was used as the base film of the thermoplastic resin layer. At this time, the thickness of the thermoplastic resin layer was 20 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 2.
[0198] [Comparative Example 3] A laminate was obtained in the same manner as in Example 1, except that nonwoven fabric N7 was used as the fiber layer and film F4 was used as the base film of the thermoplastic resin layer. At this time, the thickness of the thermoplastic resin layer was 20 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 2.
[0199] [Comparative Example 4] A laminate was obtained in the same manner as in Example 1, except that nonwoven fabric N8 was used as the fiber layer and film F5 was used as the base film of the thermoplastic resin layer. At this time, the thickness of the thermoplastic resin layer was 15 μm. No wrinkles were observed in the laminate. The results of evaluation of the obtained laminate are shown in Table 2.
[0200] [Table 2] In Examples 1 to 7, the laminate has through holes penetrating the fiber layer and the thermoplastic resin layer, the thickness ratio of the fiber layer to the thermoplastic resin layer (fiber layer / thermoplastic resin layer) is 5 to 40, and the apparent density of the laminate is 0.10 to 0.35 g / cm 3 The laminate had high radiant heat reflectivity, excellent heat insulation and breathability, and was easy to work with.
[0201] On the other hand, the laminate having no through holes in Comparative Example 1 took a long time to reduce the pressure, and therefore was poor in workability as a vacuum insulation material. In addition, the laminates having a thickness ratio (fiber layer / thermoplastic resin layer) of less than 5 and the laminates having an apparent density of 0.35 g / cm3 in Comparative Examples 2 to 4 were poor in workability as a vacuum insulation material. 3 Larger laminates had poorer thermal insulation properties.
Claims
1. A fiber layer composed of fibers mainly composed of a thermoplastic resin; A thermoplastic resin layer containing a metal; A laminate comprising: the laminate has through holes penetrating the fiber layer and the thermoplastic resin layer, a ratio of a thickness of the fiber layer to a thickness of the thermoplastic resin layer is 5 or more and 40 or less; The apparent density of the laminate is 0.10 g / cm 3 0.35g / cm or more 3 Below is the Laminate.
2. 2. The laminate according to claim 1, wherein the through holes have a diameter of 100 μm or more and 2000 μm or less, and an aperture ratio of the through holes is 0.05% or more and 9.00% or less.
3. 3. The laminate according to claim 1, wherein one of the outermost layers of the laminate is the fiber layer, and the arithmetic mean roughness Ra of the outermost layer on the fiber layer side is 3.0 μm or more and 30.0 μm or less.
4. 3. The laminate according to claim 1, wherein one of the outermost layers of the laminate is the thermoplastic resin layer, and the arithmetic mean roughness Ra of the outermost layer on the thermoplastic resin layer side is 0.01 μm or more and less than 3.00 μm.
5. 3. The laminate according to claim 1 or 2, wherein one outermost layer of the laminate is the fiber layer, and the outermost layer on the fiber layer side has an arithmetic mean roughness Ra of 3.0 μm or more and 30.0 μm or less, and the other outermost layer of the laminate is the thermoplastic resin layer, and the outermost layer on the thermoplastic resin layer side has an arithmetic mean roughness Ra of 0.01 μm or more and less than 3.00 μm.
6. The laminate according to claim 1 or 2, further comprising a metal layer containing aluminum on at least one surface of the thermoplastic resin layer.
7. 3. The laminate according to claim 1, wherein one outermost layer of the laminate is a long-fiber nonwoven fabric layer.
8. A heat insulating material comprising the laminate according to claim 1 or 2.
9. A vacuum insulated container comprising the heat insulating material according to claim 8.
10. The method for producing a laminate according to claim 1 , further comprising a step of heat-sealing the fiber layer and the thermoplastic resin layer.
11. The method for producing a laminate according to claim 10 , wherein the fiber layer and the thermoplastic resin layer are thermally fused together by penetrating the fiber layer with a heated protrusion.
Citation Information
Patent Citations
Heat insulating sheet, heat insulating material, and method for manufacturing heat insulating sheet
WO2019181186A1
